Examining the role of Augmented Reality (AR) with regards to customer experience & engagement within the luxury fashion industry - Malik, Kamna (2018)
The purpose of this dissertation is to trace the role of Augmented Reality (AR) and its influence on customer experience and engagement within the luxury fashion industry. Given the recent digital advancements and the renewed use of social media, this research question is an interesting one since it examines the role of AR from a brand as well as a customer perspective. The integration of AR tools in the luxury fashion industry is relatively a new concept and thus there is limited academic literature available on it. This report aims to fill some gaps in the current research while tracing the co-relation between AR, customer experience and engagement. The theoretical background has been primarily built on key experiential marketing theories provided by Schmitt (1999), Pine and Gilmore (1998) and Holbrook and Hirschman (1982). However , different perspectives on customer experience, engagement and AR have also been studied and examined in order to draw a balanced line of argument. The thesis has been conducted through a qualitative method, where individuals have been interviewed in a semi-structured manner to examine the marketing strategies, perceptions, motivations and the overall customer experience. As a result, this is an empirical explanatory study that relies on narratives both from a brand and consumer’s point of view. The sample consisted of a brand representatives, focus group participants and customers. The findings reveal multiple perspectives, the most important one being how luxury fashion brands are using AR to engage the consumers to improve and enhance the overall shopping experience. Additionally, customers have also shared their experiences of using AR tools while shopping and have elaborated on how these tools have enhanced their overall experience with the brands. The data analysis states that the consumers are no longer looking for only ‘products.’ They are now more interested in immersive experiences that take them beyond the mere ritual of shopping and indulge their senses. Millennials are the key audience for the latest technologies especially for tools like AR. This study contributes to the existing literature by bringing together concepts of experiential marketing and luxury brands set in the context of AR in a manner that has not been pursued by before. It presents narratives both from a brand’s and customer’s perspective and offers insights that have not been deeply explored before. (Keywords: customer experience; experiential marketing; customer engagement; luxury fashion brands; Augmented Reality (AR) )